A companion to James of Viterbo - Côté, Antoine (Brill's companions to the Christian tradition, 2018)
Ten leading scholars team up to produce the first book-length treatment of the philosophical thought of James of Viterbo, one of the key thinkers at Paris in the late thirteenth century. The book examines all major areas of James's philosophical thought, exploring his connections with other important masters of the time and highlighting his originality in the context of late medieval philosophy. Contributors are: Antoine Côté, Stephen D. Dumont, R. W. Dyson, Mark D. Gossiaux, Mark Henninger, Thomas Osborne Jr., Martin Pickavé, Eric L. Saak, Jean-Luc Solère, and Gianpiero Tavolaro.